Life Threatening and Fatal Contrast Media Reactions: Pathomechanisms, Diagnosis, Prevention and Drug Management - Morcos, S. K. (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2006)
Serious or fatal reactions to a contrast agent are usually unpredictable and the majority occurs within 20 min of administration. Incidence of very severe reactions with the use of low osmolar non ionic contrast media (CM) is very low (0.004%) and is reduced by a factor of 10 in comparison to high osmolar CM (0.04%). Fatality due to CM injection is rare and the incidence is similar with both types of CM (1 in 170,000 contrast examinations). History of serious reaction to CM, bronchial asthma or multiple allergies increases the incidence of serious reactions by at least a factor of 5 in comparison to subjects with a negative history. Serious or fatal reaction to CM could be due to direct effect on basophils and mast cells or IgE mediated (type 1 hypersensitivity reaction). Activation of the kinin system leading to the formation of bradykinin could also be involved. Complement activation is probably a secondary phenomenon rather than a primary factor in initiating a serious reaction to CM. Measuring serum tryptase is important in diagnosing serious or fatal reaction to CM. Measuring IgE antibodies remains not widely available but should be considered in appropriate cases if the technique is available. Avoiding CM administration in patients at high risk of serious reaction is advisable but if the administration is deemed essential all precautions should be implemented and measures to treat serious reactions should be readily available. Oxygen supplementation, intravenous administration of physiological fluids and intramuscular injection of 0.5ml adrenalin (1:1,000) should be considered in the first line management of acute anaphylaxis. The ability to assess and treat serious CM reaction effectively is an essential skill that the radiologist should have and maintain.
Keywords: prevention